Evaluation of Storage Length to Blood Component Platelet Concentrate Quality in the Blood Bank, Dr. Soetomo General Hospital, Surabaya, Indonesia - Dhinasty Armenia1 , Betty Agustina Tambunan2,3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Storage of Platelet Concentrate (PC) can cause changes in thrombocyte quality that affect thrombocyteviability and decrease hemostatic function. All biochemical, structural and functional changes to plateletsduring storage in the Blood Bank are known as platelet storage lesions. To analyze the effect of storagelength on changes in thrombocyte morphology and function as well as the metabolic parameters of plateletconcentrate bag components. This was an analytical study with time series design. Sampling was doneconsecutively. Samples were new PC bags which were processed and stored at room temperature withagitation during June-July 2019 in the Blood Bank of the Dr. Soetomo General Hospital, Surabaya.Examination of platelet count and MPV were performed to determine morphological changes and metabolicparameters like pH, pCO2, and pO2 on day 1, day 3, and day 5th. Data were analyzed by using Shapiro-Wilktest, Paired t test and Wilcoxon Signed Rank Test. There were significant changes in MPV, pH, and pCO2values during storage (p <0.05). However, there were no significant changes in platelet count and pO2value. Metabolic changes in PC bag were obtained but there was no decrease in platelet count so that the PCcomponent was still feasible to be given to the patient. Further research is needed for other parameters thatcan be affected by the storage process.